ANALISIS PENDIDIKAN DAN DISIPLIN KERJA TERHADAP KINERJA PERANGKAT DESA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Kusno, Riski Maulana Tri; Hamdun, Edy Kusnadi; Tulhusnah, Lusiana (Fakultas Ekonomi dan Bisnis, 2023)
The aim of the study is to analyze Education and Work Discipline on the Performance of Village Officials with Job Satisfaction as an Intervening Variable (Case Study at the Kilensari Village Office, WringinAnom Village, SumberKolak Village. Panarukan District, Situbondo Regency). The sampling technique used in this research was a saturated sample with a sample size of 40 village officials. Data analysis and hypothesis testing in this research used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that education has a positive and significant effect on job satisfaction, work discipline has a significant positive effect on job satisfaction, education has a positive but not significant effect on performance, education has a positive but not significant effect on performance, satisfaction work has a significant positive effect on performance, education has a significant positive effect on performance through job satisfaction, work discipline has a significant positive effect on performance through job satisfaction.